Managing Student Support: A Holistic Approach - Dexter, Hilary; Petch, Jim (Proceedings of the International Conference on Networked Learning, 2006)
With the advance and scaling up of e-learning and distance learning provision, the scope of student support systems has extended and deepened, demanding consideration of the methods for its planning and implementation. Management of student support is used as an example of a key business process that is one part of a higher education enterprise’s end-to-end process of e-learning provision, with a model-driven, holistic approach to its management. The proposed management method is based on implementing workflow process models that are supported by a context sensitive knowledgebase. The modelling approach already developed is advanced by the introduction of the idea of bridging principles.